Copper-cobalt oxide electrode, preparation method and application of copper-cobalt oxide electrode in preparation of 2, 5-furandicarboxylic acid
By electrodepositing CuCo2O4 electrodes on carbon fiber substrate materials and electrocatalyzed HMF to prepare FDCA, the existing process cost, high energy consumption and safety hazards are solved, and high efficiency, low energy consumption and high safety FDCA preparation is achieved.
Patent Information
- Application Number
- CN202411909787.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing HMF oxidation process is costly, energy consumption is high, and production safety risks are present, making it difficult to efficiently prepare high value-added 2,5-furandicarboxylic acid (FDCA).
The CuCo2O4 double transition metal composite oxide electrode was deposited on the carbon fiber substrate material by electrodeposition method, which was used to prepare FDCA by electrocatalytic oxidation of HMF.
The HMF conversion rate is as high as 97%, the FDCA yield is as high as 90%, the selectivity is as high as 93%, and the Faraday efficiency is as high as more than 86%, which reduces cost and energy consumption and improves process safety.
Smart Images

Figure CN119685869A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of 5-hydroxymethylfurfural electrocatalytic oxidation, and specifically relates to a copper-cobalt oxide electrode, a preparation method and application thereof in the preparation of 2,5-furandicarboxylic acid. Background Art
[0002] With the shortage of oil, natural gas and other fossil fuels, biomass resources have become the main competitor due to their renewability and huge reserves. 5-Hydroxymethylfurfural (HMF) is considered to be a widely used compound that can be obtained from biomass resources and has great potential in industry. For example, 2,5-furandicarboxylic acid (FDCA) can be prepared by oxidation of HMF, and this preparation method is expected to replace the existing petroleum-based monomer terephthalic acid as a green alternative. Although the oxidation of HMF has been studied for many years, most reports are in high pressure O 2 The synthesis method is completed by high-temperature thermal catalytic conversion using various heterogeneous catalysts containing precious metals (such as Pt, Au and Pd, etc.) under certain conditions. This synthesis method is not only costly and energy-intensive, but also has great production safety risks. Therefore, it is still a huge challenge to develop a new FDCA synthesis method with high catalytic activity, high selectivity and low energy.
[0003] Electrocatalytic oxidation is a green and efficient method that can generate FDCA with high selectivity and high yield at room temperature and pressure, and can also simultaneously achieve low-voltage water electrolysis to produce hydrogen. This method can avoid the high temperature and high pressure of O 2 In addition, the electrochemical method of conversion under normal temperature and pressure conditions can use clean and sustainable water as an oxygen source to transfer the active oxygen species of the oxidation electrocatalyst, thereby greatly reducing O 2 Currently, transition metal oxides are widely used in the electro-oxidation of small molecules due to their unique eg hybrid orbitals and abundant 3d electron numbers. In particular, CuO is a promising electrocatalyst for the catalytic oxidation of HMF. However, due to the weak adsorption and activation ability of OH- and HMF molecules, the intrinsic HMF oxidation activity of CuO is still far from meeting practical needs. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the above-mentioned shortcomings and deficiencies of the prior art, the present invention provides a copper-cobalt oxide electrode, a preparation method and its application in the preparation of 2,5-furandicarboxylic acid, and deposits CuCo on a carbon fiber substrate by electrodeposition. 2 O 4, thereby preparing an electrode of a double transition metal composite oxide, which is used for electrocatalytic oxidation of HMF to prepare FDCA, so that the HMF conversion rate is as high as 97%, the FDCA yield is as high as 90%, the selectivity is as high as 93%, and the Faraday efficiency is over 86%; therefore, the present invention provides a method for synthesizing FDCA with high catalytic activity, high selectivity and low energy, which solves the technical problems of high cost, high energy consumption and potential safety hazards in the existing HMF oxidation process.
[0006] (II) Technical solution
[0007] In a first aspect, the present invention provides a method for preparing a copper-cobalt oxide electrode, comprising the following steps:
[0008] S1. providing a mixed salt solution containing copper salt and cobalt salt, wherein the total concentration of copper ions and cobalt ions contained in the mixed salt solution is 0.1-0.2 mol / L;
[0009] S2, using the mixed salt solution as the electrolyte, using the purified carbon fiber felt as the working electrode and Pt as the counter electrode to perform constant potential deposition at room temperature; after the electrodeposition is completed, an electrode precursor with the carbon fiber felt as the matrix is obtained, and the electrode precursor is covered with copper cobalt hydroxide;
[0010] S3. calcining the electrode precursor in an air atmosphere at 300-310° C. to obtain a copper-cobalt oxide electrode.
[0011] According to a preferred embodiment of the present invention, in S1, the copper salt in the mixed salt solution is copper nitrate, and the cobalt salt is cobalt nitrate; preferably, the molar ratio of copper ions to cobalt ions is 2-8:8-2, more preferably 3:7; the total concentration of copper ions and cobalt ions contained in the mixed salt solution is 0.1 mol / L. For example, the copper ions are 0.02 mol / L, 0.03 mol / L, 0.04 mol / L, 0.05 mol / L, 0.06 mol / L, 0.07 mol / L or 0.08 mol / L, more preferably 0.03 mol / L; the cobalt ion concentration is 0.07 mol / L.
[0012] According to a preferred embodiment of the present invention, in S2, the conditions for constant potential deposition are: setting the stirring speed of the electrolyte to 750-850rpm, using Ag / AgCl electrode and saturated KCl as reference electrodes, and performing constant potential deposition for 5-10min under the condition of keeping the potential constant at 1.5V-2.5V vs.Ag / AgCl, taking out the carbon fiber felt, and obtaining an electrode precursor. By comparing with the reference electrode, the potential on the working electrode can be accurately set and maintained. This ensures that the deposition process is carried out according to a predetermined potential, thereby achieving precise control of the type, structure and morphology of the sediment.
[0013] According to a preferred embodiment of the present invention, in S2, the purified carbon fiber felt refers to the following treatment of the carbon fiber felt: cutting the carbon fiber felt to an appropriate size, ultrasonically cleaning it with deionized water, acetone, and anhydrous ethanol for 5-10 minutes each, and then vacuum drying it for use.
[0014] According to a preferred embodiment of the present invention, in S3, the calcination procedure is: in an air atmosphere, the temperature is raised to 300-310°C at a rate of 2-2.5°C, kept at this temperature for 2.5-3.5h, and then cooled to room temperature at a rate of 3-4°C to obtain a copper cobalt oxide electrode.
[0015] In a second aspect, the present invention provides a copper-cobalt oxide electrode for preparing FDCA by electrocatalytic oxidation of HMF, which is prepared by any of the above-mentioned embodiments.
[0016] In a third aspect, the present invention further provides a method for preparing FDCA by electrocatalytic oxidation of HMF, comprising: using the copper cobalt oxide electrode prepared in any of the above embodiments as a working electrode, a Hg / HgO electrode as a reference electrode, assembling a three-electrode electrolytic cell with Pt as a counter electrode, and separating the anode electrolytic cell and the cathode electrolytic cell with an anion exchange membrane;
[0017] A potassium hydroxide solution containing HMF is added to the anode electrolytic cell, and a potassium hydroxide solution with the same concentration as that of the anode electrolytic cell is added to the cathode electrolytic cell; the working electrode is installed in the anode electrolytic cell;
[0018] Under normal pressure, the voltage between the working electrode and the counter electrode is maintained at 1.0-1.5V to carry out electrolysis reaction, and FDCA is prepared in the anode electrolytic cell; during the electrolysis reaction, the temperature of the electrolyte in the electrolytic cell is maintained at 20-60°C.
[0019] According to a preferred embodiment of the present invention, the anion exchange membrane is Fumasep FAA-3-PK-130.
[0020] According to a preferred embodiment of the present invention, the initial concentration of the potassium hydroxide solution in the anode electrolytic cell and the cathode electrolytic cell is 1.0 mol / L.
[0021] According to a preferred embodiment of the present invention, hydrogen is also produced in the cathode electrolyzer.
[0022] According to a preferred embodiment of the present invention, during the electrolysis reaction, the electrolyte temperature in the electrolytic cell is maintained at 20-60°C by continuous stirring and water bath thermostating. By continuous stirring, the solution phase distribution and temperature distribution in the three-electrode electrolytic cell are kept uniform, and the temperature of the electrolyte is kept constant by a water bath. Preferably, the stirring speed is 800-1000rpm. Controlling the reaction temperature can greatly reduce side reactions, improve process safety and ensure the yield of the target product.
[0023] According to a preferred embodiment of the present invention, the initial concentration of HMF in the anode electrolytic cell is 10-40 mmol / L.
[0024] According to a preferred embodiment of the present invention, during the electrolysis reaction, the electrolyte temperature is maintained at 40°C, the electrolysis voltage is 1.1V, and the electrolysis time is more than 3 hours, preferably 3-5 hours.
[0025] (III) Beneficial effects
[0026] The present invention adopts an electrodeposition method to prepare a copper-cobalt oxide electrode with a carbon fiber felt as a substrate, and applies it to the electrocatalytic oxidation of HMF to prepare a high-value-added fine chemical FDCA, and synthesizes FDCA by electrocatalytic oxidation of HMF. The electrode has excellent electrocatalytic oxidation performance of HMF, and the yield of the obtained FDCA is as high as 90%, the HMF conversion rate is 97%, the selectivity is 93%, and the Faraday efficiency is 86%. Compared with the high-pressure O 2 The method for preparing FDCA by electrocatalytic oxidation of HMF using a heterogeneous catalyst process with precious metals under the conditions of the present invention not only has low cost and low energy consumption, but also has high conversion rate and high selectivity of reactants, and also has high process safety, and is suitable for large-scale production applications.
[0027] In the copper-cobalt oxide electrode of the present invention, copper oxide and cobalt oxide are evenly interlocked at the nanometer scale to form an overall structure in which the dissolved phase and the dispersed phase are mutually present. This composite oxide can provide a large number of interface contact areas, which is conducive to the increase of electron transfer and catalytic active sites, helps to improve catalytic efficiency, promote electron transfer (the interface between different materials can optimize the electron transfer path and reduce resistance), thereby increasing the electrochemical reaction rate, promoting synergistic effects, and further improving catalytic performance.
[0028] The high-performance copper-cobalt oxide electrode prepared by the present invention combines the excellent properties of transition metal oxides and carbon fiber felt, and has the advantages of good oxidation performance, good corrosion resistance, low cost, high temperature resistance, etc. The electrode prepared by the electrodeposition method has the advantages of simple operation, mature and controllable process, cheap and easy to obtain raw materials, etc. The process conditions for preparing the copper-cobalt oxide electrode and preparing FDCA of the present invention are mild, the electrode materials are cheap, and the synthesis process is environmentally friendly, and has a good industrial application prospect. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the SEM image of the copper-cobalt oxide electrode prepared in Example 1.
[0030] Figure 2 This is the EDS image of the copper-cobalt oxide electrode prepared in Example 1.
[0031] Figure 3Schematic diagram of the electrolytic reaction cell for the electrocatalytic oxidation of HMF to produce FDCA. DETAILED DESCRIPTION
[0032] In order to better explain the present invention and facilitate understanding, the present invention is described in detail below through specific implementation modes in conjunction with the accompanying drawings.
[0033] The catalyst commonly used for catalytic oxidation of HMF is CuO. However, due to the weak adsorption and activation ability of OH- and HMF molecules, the inherent HMF oxidation activity of CuO is still far from meeting the actual needs. Compared with monometallic oxides, there is a synergistic effect between bimetallic oxides, a larger specific surface area, and more active sites. Bimetallic oxides often have higher catalytic activity than monometallic oxides. Therefore, the present invention has developed a HMF catalytic oxidation electrode based on copper cobalt oxide. The prior art often uses co-deposition or combustion methods for composite metal oxides, but for some applications with high requirements for fine structure or component regulation, co-deposition and combustion methods are difficult to achieve ideal accuracy. The co-deposition deposition process is very random, and it is almost impossible to produce composite metal oxides with a predetermined atomic ratio, and strict safety measures are required during the operation of the combustion method because it involves high temperature and possible explosion risks. In addition, some materials are not suitable for preparation by combustion method, especially composite materials with carbon as a carrier. Therefore, the present invention adopts electrodeposition to prepare copper cobalt oxide electrodes. The advantages of electrodeposition are: Highly controllable: the thickness and composition of the deposited layer can be precisely controlled by adjusting factors such as current density and deposition time. By preparing an electrolyte with a predetermined composition, the atomic ratio of different metals in the composite metal oxide electrode can be precisely controlled. Good material uniformity: a relatively uniform and flat surface can be obtained. Strong adaptability: applicable to a variety of material systems, including metal materials and non-metallic materials. High flexibility: easy to achieve plating of complex-shaped parts.
[0034] When selecting the base material of the copper cobalt oxide electrode, the present invention uses carbon fiber felt. Compared with the equally porous and conductive foam metal material, the advantages of carbon fiber felt include: high specific surface area: carbon fiber felt has a very high specific surface area, which is conducive to increasing the loading amount of the catalyst, thereby enhancing the catalytic activity. The network pores throughout the carbon fiber felt help to increase the contact area of the electrolyte and provide a channel for gas diffusion. Good conductivity: carbon fiber felt itself is an excellent conductor, which can effectively promote electron transfer and improve the efficiency of electrochemical reactions. High mechanical strength: carbon fiber felt has excellent mechanical properties, including high strength and light weight. Good corrosion resistance: compared with metal foam materials, carbon fiber felt shows better stability and good durability to many chemical substances. Easy to process: complex structures can be formed by weaving, winding and other methods, which is convenient for designing electrodes of different shapes (such as O-type or U-type electrodes) and sizes. It has a strong binding force with a specific type of catalyst. Among metal foam materials, only the preparation process of nickel metal foam materials is relatively mature and the cost is low, while other metal foams are expensive and costly. In addition, the high density of the foamed metal may increase the overall weight of the electrode. Although the metal foam is porous, it cannot form a through network of pores, and the electrolyte contact and gas diffusion effects are poor. The metal foam substrate also has potential corrosion problems, which can easily lead to a reduced service life. In terms of flexibility of use, the metal foam material has poor flexibility of use, is not easy to shape into various shapes as needed, and has weak customized design capabilities. Therefore, the present invention selects carbon fiber felt as the electrode base material to prepare a copper cobalt oxide electrode.
[0035] The present invention is described below in conjunction with the preferred embodiments of the present invention. In each embodiment, the anion exchange membrane Fumasep FAA-3-PK-130 used in the embodiment was purchased from Shanghai Zijun Technology Co., Ltd.
[0036] Example 1
[0037] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition, the catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. This embodiment includes the following steps:
[0038] (1) Preparation of copper-cobalt oxide catalytic electrode
[0039] The hydrophilic carbon fiber felt was cut into pieces of 1 cm×1.5 cm, and cleaned in ultrasonic waves for 10 min using 20 mL of deionized water, acetone, and anhydrous ethanol, respectively, and dried in a vacuum dryer for later use.
[0040] Carbon fiber felt was used as the working electrode, Ag / AgCl electrode (saturated KCl) was used as the reference electrode, and Pt sheet was used as the counter electrode for constant potential deposition. 0.03 mol / L Cu(NO 3 ) 2 ·3H 2 O and 0.07 mol / L Co(NO 3 ) 2 6H 2 O. During the electrodeposition process, the electrolyte was continuously stirred at a speed of 800 rpm, and the potential was kept constant at 2.0 V vs. Ag / AgCl for 5 min to obtain a Cu-Co hydroxide electrode precursor.
[0041] The electrode precursor was placed in a quartz boat and placed in a tube furnace. Under air atmosphere, the heating rate was controlled to be 2°C / min. When the temperature reached 300°C, calcination was performed for 3 hours. After the reaction was completed, the cooling rate was controlled to be 3°C / min, and the temperature dropped to room temperature to finally obtain a copper-cobalt oxide electrode. Figure 1 and Figure 2 As shown, they are SEM and EDS images of the copper-cobalt oxide electrode prepared in this embodiment, and it can be seen in the figure that a variety of different atoms are embedded in each other to form an overall structure in which the dissolved phase and the dispersed phase are mutually.
[0042] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0043] The copper cobalt oxide electrode prepared in the above steps was used as the working electrode, the Hg / HgO electrode was used as the reference electrode, and the Pt electrode was used as the counter electrode to assemble a three-electrode electrolytic cell (such as Figure 3 Schematic diagram shown), the anode electrolyzer and the cathode electrolyzer are separated by an anion exchange membrane; a potassium hydroxide solution containing 20mmol / L HMF (potassium hydroxide concentration is 1.0mol / L) is added to the anode electrolyzer, and a 1.0mol / L potassium hydroxide solution is added to the cathode electrolyzer; the working electrode is installed in the anode electrolyzer, and the counter electrode is installed in the cathode electrolyzer. Under normal pressure, the voltage between the working electrode and the counter electrode is maintained at 1.1V, and the electrolysis reaction is carried out for 3h, and FDCA is prepared in the anode electrolyzer; during the electrolysis reaction, the electrolyte is continuously stirred at a speed of 800rpm, and the anode electrolyzer and the cathode electrolyzer are kept at a constant temperature of 40℃ in a water bath. After 3h of electrolysis, the anode electrolyte is quantitatively detected by liquid chromatography to determine the yield of FDCA. It has been determined that the yield, selectivity and Faraday efficiency of FDCA are 91%, 97% and 89% respectively.
[0044] Example 2
[0045] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, and a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition. The catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. Specifically, the following steps are included:
[0046] (1) Preparation of copper-cobalt oxide catalytic electrode
[0047] The hydrophilic carbon fiber felt was cut into pieces of 1 cm×1.5 cm, and cleaned in ultrasonic waves for 10 min using 20 mL of deionized water, acetone, and anhydrous ethanol, respectively, and dried in a vacuum dryer for later use.
[0048] Carbon fiber felt was used as the working electrode, Ag / AgCl electrode (saturated KCl) was used as the reference electrode, and Pt sheet was used as the counter electrode for constant potential deposition. 0.06 mol / L Cu(NO 3 ) 2 ·3H 2 O and 0.04 mol / L Co(NO 3 ) 2 6H 2 O. During the electrodeposition process, the electrolyte was continuously stirred at a speed of 800 rpm, and the potential was kept constant at 2.0 V vs. Ag / AgCl for 5 min to obtain a Cu-Co hydroxide electrode precursor.
[0049] The electrode precursor was placed in a quartz boat and placed in a tube furnace. Under air atmosphere, the heating rate was controlled to be 2°C / min. When the temperature reached 300°C, calcination was performed for 3 hours. After the reaction was completed, the cooling rate was controlled to be 3°C / min and dropped to room temperature to finally obtain a copper-cobalt oxide electrode.
[0050] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0051] Referring to the method and conditions for synthesizing FDCA by electrocatalytic oxidation of HMF in Example 1, FDCA was finally obtained in the anode electrolyzer. After the electrolysis was completed, the anode electrolyte was quantitatively detected by liquid chromatography to determine the yield of FDCA. It was determined that the yield, selectivity and Faraday efficiency of FDCA reached 73%, 88.2% and 79.3%, respectively.
[0052] Example 3
[0053] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, and a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition. The catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. Specifically, the following steps are included:
[0054] (1) Preparation of copper-cobalt oxide catalytic electrode
[0055] A copper-cobalt oxide catalytic electrode was prepared according to the same method and conditions as step (1) in Example 1.
[0056] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0057] The copper cobalt oxide electrode prepared in the above steps is used as the working electrode, the Hg / HgO electrode is used as the reference electrode, and the Pt electrode is used as the counter electrode to assemble a three-electrode electrolytic cell, and the anode electrolytic cell and the cathode electrolytic cell are separated by an anion exchange membrane; a potassium hydroxide solution containing 30mmol / L HMF (potassium hydroxide concentration is 1.0mol / L) is added to the anode electrolytic cell, and a 1.0mol / L potassium hydroxide solution is added to the cathode electrolytic cell; the working electrode is installed in the anode electrolytic cell, and the counter electrode is installed in the cathode electrolytic cell. Under normal pressure, the voltage between the working electrode and the counter electrode is maintained at 1.5V, and the electrolysis reaction is carried out for 3h, and FDCA is prepared in the anode electrolytic cell; during the electrolysis reaction, the electrolyte is continuously stirred at a speed of 800rpm, and the anode electrolytic cell and the cathode electrolytic cell are kept at a constant temperature of 30°C in a water bath. After the electrolysis for 3h, the yield of FDCA in the anode electrolyte is quantitatively detected by liquid chromatography. It was determined that the yield, selectivity and Faradaic efficiency of FDCA reached 70%, 81% and 70.7%, respectively.
[0058] Example 4
[0059] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, and a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition. The catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. Specifically, the following steps are included:
[0060] (1) Preparation of copper-cobalt oxide catalytic electrode
[0061] The hydrophilic carbon fiber felt was cut into pieces of 1 cm×1.5 cm, and cleaned in ultrasonic waves for 10 min using 20 mL of deionized water, acetone, and anhydrous ethanol, respectively, and dried in a vacuum dryer for later use.
[0062] Carbon fiber felt was used as the working electrode, Ag / AgCl electrode (saturated KCl) was used as the reference electrode, and Pt sheet was used as the counter electrode for constant potential deposition. 0.02 mol / L Cu(NO 3 ) 2 ·3H 2 O and 0.08 mol / L Co(NO 3 ) 2 6H 2O. During the electrodeposition process, the electrolyte was continuously stirred at a speed of 800 rpm, and the potential was kept constant at 2.0 V vs. Ag / AgCl for 5 min to obtain a Cu-Co hydroxide electrode precursor. The electrode precursor was placed in a quartz boat and placed in a tube furnace. Under air atmosphere conditions, the heating rate was controlled to be 2°C / min. When the temperature rose to 300°C, calcination was performed for 3 hours. After the reaction was completed, the cooling rate was controlled to be 3°C / min and dropped to room temperature to finally obtain a copper-cobalt oxide electrode.
[0063] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0064] Referring to the method and conditions for synthesizing FDCA by electrocatalytic oxidation of HMF in Example 1, FDCA was finally obtained in the anode electrolyzer. After the electrolysis was completed, the anode electrolyte was quantitatively detected by liquid chromatography to determine the yield of FDCA. It was determined that the yield, selectivity and Faraday efficiency of FDCA reached 84%, 90.3% and 86.6%, respectively.
[0065] Example 5
[0066] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, and a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition. The catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. Specifically, the following steps are included:
[0067] (1) Preparation of copper-cobalt oxide catalytic electrode
[0068] The hydrophilic carbon fiber felt was cut into pieces of 1 cm×1.5 cm, and cleaned in ultrasonic waves for 10 min using 20 mL of deionized water, acetone, and anhydrous ethanol, respectively, and dried in a vacuum dryer for later use.
[0069] Carbon fiber felt was used as the working electrode, Ag / AgCl electrode (saturated KCl) was used as the reference electrode, and Pt sheet was used as the counter electrode for constant potential deposition. 0.05 mol / L Cu(NO 3 ) 2 ·3H 2 O and 0.05 mol / L Co(NO 3 ) 2 6H 2 O. During the electrodeposition process, the electrolyte was continuously stirred at a speed of 800 rpm, and the potential was kept constant at 2.0 V vs. Ag / AgCl for 5 min to obtain a Cu-Co hydroxide electrode precursor. The electrode precursor was placed in a quartz boat and placed in a tube furnace. Under air atmosphere conditions, the heating rate was controlled to be 2°C / min. When the temperature rose to 300°C, calcination was performed for 3 hours. After the reaction was completed, the cooling rate was controlled to be 3°C / min and dropped to room temperature to finally obtain a copper-cobalt oxide electrode.
[0070] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0071] Referring to the method and conditions for synthesizing FDCA by electrocatalytic oxidation of HMF in Example 1, FDCA was finally obtained in the anode electrolyzer. After the electrolysis was completed, the anode electrolyte was quantitatively detected by liquid chromatography to determine the yield of FDCA. It was determined that the yield, selectivity and Faraday efficiency of FDCA reached 82%, 87.8% and 78.5%, respectively.
[0072] Example 6
[0073] In this embodiment, hydrophilic carbon fiber felt is used as a substrate, and a copper-cobalt oxide catalytic electrode is prepared by constant potential electrodeposition. The catalytic electrode is used as an anode, and HMF is electrolytically catalyzed to synthesize FDCA. Specifically, the following steps are included:
[0074] (1) Preparation of copper-cobalt oxide catalytic electrode
[0075] A copper-cobalt oxide catalytic electrode was prepared according to the same method and conditions as step (1) in Example 1.
[0076] (2) Electrocatalytic oxidation of HMF to synthesize FDCA
[0077] The copper cobalt oxide electrode prepared in the above steps is used as the working electrode, the Hg / HgO electrode is used as the reference electrode, and the Pt electrode is used as the counter electrode to assemble a three-electrode electrolytic cell, and the anode electrolytic cell and the cathode electrolytic cell are separated by an anion exchange membrane; a potassium hydroxide solution containing 20mmol / L HMF (potassium hydroxide concentration is 1.0mol / L) is added to the anode electrolytic cell, and a 1.0mol / L potassium hydroxide solution is added to the cathode electrolytic cell; the working electrode is installed in the anode electrolytic cell, and the counter electrode is installed in the cathode electrolytic cell. Under normal pressure, the voltage between the working electrode and the counter electrode is maintained at 1.2V, and the electrolysis reaction is carried out for 4h, and FDCA is prepared in the anode electrolytic cell; during the electrolysis reaction, the electrolyte is continuously stirred at a speed of 800rpm, and the anode electrolytic cell and the cathode electrolytic cell are kept at a constant temperature of 60℃ using a water bath. After the electrolysis for 3h, the yield of FDCA in the anode electrolyte is quantitatively detected by liquid chromatography. It was determined that the yield, selectivity and Faradaic efficiency of FDCA reached 76%, 83.4% and 73.9%, respectively.
[0078] By comparing the above examples, it can be found that when preparing a copper-cobalt oxide electrode, when the molar ratio of copper ions to cobalt ions is 3:7 and the total concentration of copper ions and cobalt ions contained in the mixed salt solution is 0.1 mol / L, the electrodeposition potential is constant at 2.0V vs. Ag / AgCl for 300s, and the prepared copper-cobalt oxide electrode has the best electrocatalytic efficiency. When using the cobalt oxide electrode to prepare FDCA by electrocatalytic oxidation of HMF, the anode tank electrolyte is 1.0 mol / L potassium hydroxide solution and 20 mmol / L HMF solution, the electrolysis temperature is constant at 40°C, the voltage is 1.1V for 3h, and the yield, selectivity and Faraday efficiency of the final target product FDCA are the highest.
[0079] Comparative Example 1
[0080] In this comparative example, the carbon fiber felt is replaced with a foam copper of equal size on the basis of Example 1, and 20 mL of deionized water, acetone, and anhydrous ethanol are used in turn to clean in an ultrasonic wave for 10 minutes, put into a vacuum dryer and dry for standby use. Next, the method and conditions for preparing the copper cobalt oxide electrode in Example 1 are operated to obtain a copper cobalt oxide electrode with a foam copper as a substrate. The prepared copper cobalt oxide electrode is used as an anode, and the electrocatalytic oxidation of HMF is carried out according to the step (2) method in Example 1 to synthesize FDCA. After the electrolysis is completed, the anolyte is quantitatively detected by liquid chromatography to determine the yield of FDCA therein. The yield, selectivity, and Faraday efficiency of FDCA are measured to reach 84.2%, 87.8%, and 79.9%, respectively. Among them, in the process of calcining the electrode precursor to prepare the copper cobalt oxide electrode, the conductivity of the foam copper is significantly reduced due to the generation of a large amount of cuprous oxide on the surface, resulting in a significant decrease in the catalytic performance and Faraday efficiency of the electrode.
[0081] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a copper-cobalt oxide electrode, characterized in that: The steps include: S1. providing a mixed salt solution containing copper salt and cobalt salt, wherein the total concentration of copper ions and cobalt ions contained in the mixed salt solution is 0.1-0.2 mol / L; S2, using the mixed salt solution as the electrolyte, using the purified carbon fiber felt as the working electrode and Pt as the counter electrode to perform constant potential deposition at room temperature; after the electrodeposition is completed, an electrode precursor with the carbon fiber felt as the matrix is obtained, and the electrode precursor is covered with copper cobalt hydroxide; S3. calcining the electrode precursor in an air atmosphere at 300-310° C. to obtain a copper-cobalt oxide electrode.
2. The preparation method according to claim 1, characterized in that: In S1, the copper salt in the mixed salt solution is copper nitrate, and the cobalt salt is cobalt nitrate; preferably, the molar ratio of copper ions to cobalt ions is 3:7; and the total concentration of copper ions and cobalt ions contained in the mixed salt solution is 0.1 mol / L.
3. The preparation method according to claim 1, characterized in that: In S2, the conditions for constant potential deposition are: setting the stirring speed of the electrolyte to 750-850 rpm, using Ag / AgCl electrode and saturated KCl as reference electrodes, and performing constant potential deposition for 5-10 minutes under the condition of keeping the potential constant at 1.5V-2.5V vs.Ag / AgCl, taking out the carbon fiber felt, and obtaining an electrode precursor.
4. The preparation method according to claim 1, characterized in that: In S2, the purified carbon fiber felt refers to the following treatment of the carbon fiber felt: cutting the carbon fiber felt to an appropriate size, ultrasonically cleaning it with deionized water, acetone, and anhydrous ethanol for 5-10 minutes each, and then vacuum drying it for standby use.
5. The preparation method according to claim 1, characterized in that: In S3, the calcination procedure is: in an air atmosphere, the temperature is raised to 300-310°C at a rate of 2-2.5°C, kept at this temperature for 2.5-3.5h, and then cooled to room temperature at a rate of 3-4°C to obtain a copper cobalt oxide electrode.
6. A copper-cobalt oxide electrode for preparing 2,5-furandicarboxylic acid by electrocatalytic oxidation of 5-hydroxymethylfurfural, which is prepared by the preparation method according to any one of claims 1 to 5.
7. A method for preparing 2,5-furandicarboxylic acid by electrocatalytic oxidation of 5-hydroxymethylfurfural, characterized in that: include: A three-electrode electrolytic cell is assembled using the copper-cobalt oxide electrode of claim 6 as a working electrode, a Hg / HgO electrode as a reference electrode, and Pt as a counter electrode, wherein the anode electrolytic cell and the cathode electrolytic cell are separated by an anion exchange membrane; A potassium hydroxide solution containing HMF is added to the anode electrolytic cell, and a potassium hydroxide solution with the same concentration as that of the anode electrolytic cell is added to the cathode electrolytic cell; the working electrode is installed in the anode electrolytic cell; Under normal pressure, the voltage between the working electrode and the counter electrode is maintained at 1.0-1.5V to carry out electrolysis reaction, and FDCA is prepared in the anode electrolytic cell; during the electrolysis reaction, the temperature of the electrolyte in the electrolytic cell is maintained at 20-60°C.
8. The method according to claim 7, characterized in that The initial concentration of potassium hydroxide solution in the anode electrolytic cell and the cathode electrolytic cell was 1.0 mol / L.
9. The method according to claim 7, characterized in that: During the electrolysis reaction, the electrolyte temperature in the electrolytic cell is maintained at 20-60°C by continuous stirring and water bath thermostat; the stirring speed is 800-1000rpm.
10. The method according to claim 7, characterized in that The initial concentration of HMF in the anode electrolyzer is 10-40 mmol / L; a hydrogen collection device is set in the cathode electrolyzer.
Citation Information
Patent Citations
Production method of composite metal oxide functional electrode
CN110818031A